PENGEMBANGAN INOVASI KEMASAN PRODUK UNTUK MENINGKATKAN DAYA TARIK UMKM DI DESA TEROS - Amanda, Nadia Desya; Wuryantoro, Javier Atallariz; Paramarta, M.Magistra Apta; Wulan Sari, Nova Lailan; Rahman, Fitri Aulia; Syahrul, M; Sonia, Eva; Hafidz Hamidah Yusuf, Abdul; Nurajizah, Nurajizah; Hafidah, Nur; Nurchayati, Nurchayati (Universitas Mataram, 2025)
Real Work Lectures are a form of education by providing learning experiences for students to live in society. MSMEs are a sector that is quite important in playing various real economic interests in national development, especially for the creation of new businesses and jobs.This activity aims to explain the efforts that can be made to increase the marketing of MSME products in Teros Village, Labuhan Haji District, East Lombok Regency through optimizing packaging innovation. The method used consists of three stages: planning, implementation and evaluation. Assistance is provided by assisting in making branding labels. From the results of this activity, it can be concluded that direct assistance is more effective in increasing the awareness of MSMEs to adopt packaging innovations.